Recent Progress in Magnetic Resonance Imaging of the Embryonic and Neonatal Mouse Brain - Wu, Dan; Zhang, Jiangyang (Frontiers in Neuroanatomy, 2016)
The laboratory mouse has been widely used as a model system to investigate the genetic control mechanisms of mammalian brain development. Magnetic resonance imaging (MRI) is an important tool to characterize changes in brain anatomy in mutant mouse strains and injury progression in mouse models of fetal and neonatal brain injury. Progress in the last decade has enabled us to acquire MRI data with increasing anatomical details from the embryonic and neonatal mouse brain. High-resolution ex vivo MRI, especially with advanced diffusion MRI methods, can visualize complex microstructural organizations in the developing mouse brain. In vivo MRI of the embryonic mouse brain, which is critical for tracking anatomical changes longitudinally, has become available. Applications of these techniques may lead to further insights into the complex and dynamic processes of brain development.